Evidence and belief in regulatory decisions – incorporating expected utility into decision modelling - Li, Jiawei; Davies, G.J.; Kendall, G.; Soane, E.; Bai, R.; Rocks, S.A.; Pollard, S.J.T. (Elsevier, 2012)
Recent changes in the assessment and management of risks has had the effect that greater importance has been placed on relationships between individuals and within groups to inform decision making. In this paper, we provide the theoretical underpinning for an expected utility approach to decision-making. The approach, which is presented using established evidence support logic (TESLA™), integrating the expected utilities in the forming of group decisions. The rationale and basis are described and illustrated through a hypothetical decision context of options for the disposal of animal carcasses that accumulate during disease outbreaks. The approach forms the basis for exploring the richness of risk-based decisions, and representing individual beliefs about the sufficiency of evidence they may advance in support of hypotheses.